Revealing the City Influence and Its Pattern Using Web Search Data: A New Perspective Through Attention Flow - Xiaoxiao Wang; Haiping Zhang; Zitong Li; Xin Yang; Ziyi Qian; Duo Bian; Yongxin Zhao (ISPRS International Journal of Geo-Information)
City influence is a critical topic in regional studies, reflecting how cities draw attention and exert impact in various domains. Understanding city influence is essential for fostering sustainable urban growth. However, existing studies have failed to fully explore the characteristics of city influence reflected by collective behaviors from a bottom-up perspective. This study investigates how individual search behaviors mirror the attention cities attract, providing insights into their perceived influence. An “attention flow” model is developed to differentiate between cities that draw significant interest and those that show a strong preference for these influential hubs. This research focuses on cities in China, analyzing the spatial patterns and factors that affect city influence using spatial statistical methods. The results show that 69% of the cities that exhibit a strong preference are geographically closer to the more influential cities, emphasizing the role of geographical proximity in shaping urban influence in the digital age. Additionally, the study reveals patterns of power dislocation, partnership, and siphoning between cities. A consistent relationship is identified between influential cities and their more connected cities, particularly where administrative hubs tend to attract nearby cities focused on science and education. This research deepens our understanding of how city influence is shaped by digital behaviors and spatial relationships, providing insights for policymakers to foster balanced regional development and enhance inter-city cooperation.